TINJAUAN YURIDIS PERCERAIAN ATAS PERKAWINAN YANG TIDAK TERCATAT DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA MEDAN - Devi, Ria Sintha (Pascasarjana UDA, 2019)
The legal basis in implementing marriage in Indonesia is Law Num of 1974 concerning Marriage. The Department of Population and Civil Registration is in charge of data administration and issuing written evidence regarding marriage and divorce. The research problems of this study are (1)What is the effect of the divorce law on marriage that is not recorded in the Population and Civil Registration Service? (2) What things are considered by the judge in deciding divorce on marriage that is not recorded in the Population and Civil Registration Service? (3) How is the Role of the Population and Civil Registration Service against Divorce on Marriage that is not recorded in the Population and Civil Registration Service? Research method used is normative juridical using secunder data. Library research was applied in this study to collect data by means of library research, namely data collection by reviewing library materials or secondary data which includes primary legal materials, secondary legal materials and tertiary legal materials. The legal effect of divorce on marriage that is not recorded in the Department of Population and Civil Registration is that the marriage does not have permanent legal force and is not recognized in applicable law.The judge's consideration in deciding divorce against marriage that is not recorded by the Population and Civil Registration Service is by looking at the legal facts submitted by the plaintiff and the defendant as in the Medan District Court Decision No. 431 / Pdt.G / 2010 / PN-MDN that is based on the Letter of Marriage Certificate and witness testimony and other evidences. Problem solving from divorce whose marriage was not recorded by the Population and Civil Registration Service arrived at the court stage. The Medan City Population and Civil Registration Service cannot issue a divorce certificate if there is no marriage certificate. Study of the decision of the Medan District Court No. 431 / Pdt.G / 2010 / PN-MDN, Medan City Population and Civil Registration Office cannot issue divorce certificates because there is no marriage certificate.